2015
DOI: 10.1117/1.jei.24.3.033023
|View full text |Cite
|
Sign up to set email alerts
|

Underwater image enhancement by dehazing and color correction

Abstract: Poor visibility due to the effects of light absorption and scattering is challenging for processing underwater images. We propose an approach based on dehazing and color correction algorithms for underwater image enhancement. First, a simple dehazing algorithm is applied to remove the effects of haze in the underwater image. Second, color compensation, histogram equalization, saturation, and intensity stretching are used to improve contrast, brightness, color, and visibility of the underwater image. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Experiments have shown that although the color related to short wavelength can be enhanced, the method used is limited by the accuracy of the optical model and parameter estimation; Reference [5] proposed a Rayleigh-distributed color model fusion method, which not only reduced image noise, but also improved the contrast of the image to a certain extent, but led to excessive image enhancement; The enhancement method of underwater image based on defogging and color correction proposed in [6], although it solves the interference of noise and fog, however, there may also be problems with insufficient or excessive image enhancement; Reference [7] used a single underwater image restoration method by combining the blue-green channel and the red channel.…”
Section: 1research Status and Problemsmentioning
confidence: 99%
“…Experiments have shown that although the color related to short wavelength can be enhanced, the method used is limited by the accuracy of the optical model and parameter estimation; Reference [5] proposed a Rayleigh-distributed color model fusion method, which not only reduced image noise, but also improved the contrast of the image to a certain extent, but led to excessive image enhancement; The enhancement method of underwater image based on defogging and color correction proposed in [6], although it solves the interference of noise and fog, however, there may also be problems with insufficient or excessive image enhancement; Reference [7] used a single underwater image restoration method by combining the blue-green channel and the red channel.…”
Section: 1research Status and Problemsmentioning
confidence: 99%
“…As a result, the effects of haze from scattering and the distortion from color cast can be reduced. Li and Guo 22 proposed an underwater image-enhancement method based on a dehazing algorithm and a filtering algorithm. Serikawa and Lu 19 addressed the problems of scattering and color cast for underwater images by compensating the attenuation discrepancy along the propagation path.…”
Section: Related Workmentioning
confidence: 99%
“…Chani and Isa [15] improved the contrast and reduced the noise of underwater images through integrated color model with Rayleigh distribution. Li and Guo [16] proposed an underwater image enhancement method based on dehazing and color correction. However, underwater image enhancement technique usually produces under-enhanced or over-enhanced regions because this kind of technique is not based on the underwater imaging model.…”
Section: Introductionmentioning
confidence: 99%